ANALISIS GANGGUAN HUBUNG SINGKAT PADA JARINGAN PEMAKAIAN SENDIRI PLTU BOLOK PT. SMSE (IPP) UNIT 3 DAN 4 MENGGUNAKAN SOFTWARE ETAP 12.6.0 - Agusthinus S. Sampeallo; Nursalim Nursalim; Patrisius J. Fischer (Jurnal Media Elektro, 2019)
Bolok Steam Power Plant has its own 6.3 kV usage network to service loads such as Feed Water Pump and Circulating Pump Feed. This self-use network is expected to supply unit loads at the Bolok coal-fired steam power plant without any interference. The presence of disturbances such as short circuit in the electric power system can cause problems such as damage to electrical equipment and the emergence of a power outage. Therefore problems that arise like this require an analytical study to determine the short circuit current that will occur while reducing the consequences that arise. This study aims to determine the largest short circuit fault current with the help of ETAP 12.6.0 software. Short circuit simulation results with ETAP 12.6.0 will be compared with manual calculations based on positive, negative and zero sequence impedance values from the point of disturbance location. Based on the results of the research that has been done, it is known that the type of two-phase short circuit interference to the ground is the largest type of interference, which is equal to 10,615 kA on the generator bus. Whereas for the smallest type of short circuit interference is the type of disturbance one phase to the ground that is equal to 3,967 kA on the OutGoing II bus. From the results of the simulations conducted, it can also be seen that changes in the value of short circuit fault currents are affected by changes in the number of operating loads. The more load that operates the positive and negative sequence impedance the smaller and the value of the short circuit current will be greater, while the zero sequence impedance does not affect the amount of load operating, as well as the opposite.